Sound-based sensing for snore signal analysis - Chua, Wan Yi. (2012)
Obstructive sleep apnea is a significant medical problem affecting up to 4 percent of middle-aged adults. The most common complaints are loud snoring with disrupted sleep and excessive daytime sleepiness and patients with apnea suffer from fragmented sleep and may develop cardiovascular abnormalities because of the repetitive cycles of snoring, airway collapse and arousal.Snoring is the most common symptom and they are reported to contain vital information in the diagnosis of sleep disorders which relies on the expertise of the clinician that inspects whole night polysomnography (PSG) recordings. This inspection is time consuming and uncomfortable for the patient. However, evaluation of the success of these methods also relies on subjective criteria and the expertise of the clinician. Thus, there is a strong need for a tool to analyze the snore signals.